Lethal exacerbation of Pneumocystis carinii pneumonia in severe combined immunodeficiency mice after infection by pneumonia virus of mice (The Rockefeller University Press, 1993)
Mice homozygous for the mutant allele scid (severe combined immunodeficiency) have been described as excellent models for Pneumocystis carinii (Pc) pneumonia (PCP), a major health problem in patients with acquired immune deficiency syndrome (AIDS) and other immunodeficiency states. Other microorganisms have been shown to infect AIDS patients simultaneously with Pc, but whether one opportunist is able to directly influence the pathogenicity of another has not been determined previously. We have deliberately coinfected scid mice (with extent Pc infection) with a variety of primarily pneumotropic viruses and bacteria and have identified pneumonia virus of mice as causing a dramatic increase in the density of Pc organisms and the morbidity due to PCP in immunodeficient scid mice. This finding has clinical significance in the management of PCP, in that the identification and treatment of coinfecting pneumotropic pathogens may be as important as treatment targeted at Pc. A search for other synergistic (or antagonistic) microorganisms and determination of their mechanism(s) of action in altering the progression of PCP is indicated.